(untitled) (International Journal of Physiology, 2019)
Background Diabetic Autonomic Neuropathy is among the least recognized and understood complications of diabetes despite its significant negative impact on survival and quality of life in people with diabetes. Objective to analyze short term frequency domain of Heart Rate Variability (HRV) in newly diagnosed diabetic patients with and without autonomic neuropathy and compare the results with controls. Method The study was conducted in medical OPD of Bapuji Hospital and Chigateri General Hospital attached to J.J.M. Medical College, Davangere. 100 consecutive newly diagnosed type 2 diabetic patients age 35 to 50 years and 50 normal individuals formed the subjects of the study. Results The age of subjects ranged from 30–60 years. The resting heart rate was significantly higher in diabetics than normal. When the blood pressure response to supine to standing was evaluated there was a significant decrease in systolic blood pressure among controls and cases. The Valsalva ratio was decreased in diabetics as compared to controls. No difference was observed in E/I ratio between control and diabetics. There was increase in systolic blood pressure during test as compared to rest. Ratio of heart rate on standing (30: 15) decreased in cases as compared to controls. Conclusion Clinical observations should not be the sole basis for the diagnosis of cardiovascular autonomic dysfunction. Screening for abnormalities is infrequently done.